Nutritional value and fatty acid composition of some traditional Argentinean meat sausages - Romero, Mara Cristina (2013)
The aim of this work was to determine the nutritional composition (moisture, protein, carbohydrates, and total fat) of meat products elaborated in the northeast of Argentina, analyzing fatty acids composition, PUFA/SFA ratio, n-6/n-3 relation, and CLA content. Thirty traditional meat products from different processes were used. Samples were classified into 4 different categories as follows: salamín (dry cured and fermented sausage), chorizos (raw sausage), chorizo ahumado (cooked and smoked sausage) and morcilla (cooked sausage). From the results, by comparison with databases from other regions of Argentina, USA and Spain, total carbohydrate contents of the salamín studied were slightly lower; fat content of raw chorizo was significantly lower, and protein content of chorizo ahumado was significantly higher. Except for chorizo, which has a lower value than 0.4, the PUFA/SFA-stearic relation of the others products were a bit higher than those reported by other researchers. CLA contents between 0.03% and 0.19 % were detected. Data obtained in this research allow to conclude that salamín elaborated in the northeast of Argentina show high protein and PUFA contents, and low atherogenic and thrombogenic indexes, which makes it a more healthful product than those of similar composition from other countries.